Prevalence and characteristics for mental health disorder before and after childhood cancer diagnosis—a statewide population-based study among Medicaid beneficiaries - Lei, Feitong; McLouth, Laurie E.; Durbin, Eric B.; Tucker, Thomas T.; Villano, John L.; Huang, Bin (Frontiers in Psychology, 2026)
IntroductionPediatric cancer patients suffer mental health deficits. Patients who are vulnerable with respect to socioeconomic or other sociodemographic factors may be at heightened risk for worse mental health outcomes during cancer for many reasons including entering treatment with an existing mental health disorder. The purpose of this study was to describe the prevalence and trajectory of mental health before and after a childhood cancer diagnosis in a socio-demographically at-risk sample.MethodsData from the Kentucky Cancer Registry was utilized to identify patients aged 19 or under with a first primary childhood cancer diagnosis during 2001–2017. Linking KCR data with Medicaid claims, we included patients with continuous Medicaid enrollment 12 months before and after their cancer diagnosis. MHDs were identified using both International Classification of Diseases (ICD)-9 and ICD-10 diagnosis codes in Medicaid claims.ResultsOf the 978 patients, 54% were male, and 39% were from Appalachian counties. The most common cancers diagnosed were leukemias (n = 238), brain and central nervous system (n = 220), and lymphomas (n = 147). For the 12-month pre-cancer diagnosis period, 32% (n = 310) of the patients had a MHD, increasing to 55% (n = 540) in the 12 months post-diagnosis period. The most frequent MHDs were mood disorder (before n = 120; after n = 311) and neuropsychiatric/developmental disorders (before n = 228; after n = 267). Mood disorders increased from 12% pre-cancer diagnosis to 32% post-cancer diagnosis, from 10 to 37% for lymphoma patients, and from 15 to 64% for bone cancer patients.ConclusionOver half of the Medicaid-enrolled childhood cancer patients in Kentucky diagnosed with MHDs within a year of their cancer diagnosis, with a notable increase from pre-diagnosis levels. This increased prevalence post-diagnosis may result from the identification of pre-existing MHDs during cancer treatment, or the emergence of new MHD because of the cancer diagnosis and treatment. Our study highlights the psychosocial needs that extend beyond standard cancer treatment and underscores the importance of psychosocial services during and after the cancer treatment period.